2017
DOI: 10.1093/nutrit/nux015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high iron intake on cognition and neurodegeneration in humans and in animal models: a systematic review

Abstract: ContextAccumulation of brain iron is linked to aging and protein-misfolding neurodegenerative diseases. High iron intake may influence important brain health outcomes in later life.ObjectiveThe aim of this systematic review was to examine evidence from animal and human studies of the effects of high iron intake or peripheral iron status on adult cognition, brain aging, and neurodegeneration.Data SourcesMEDLINE, Scopus, CAB Abstracts, the Cochrane Central Register of Clinical Trials, and OpenGrey databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 88 publications
0
55
0
1
Order By: Relevance
“…Particularly in populations living at HA this may expose to iron overload. Recently, a systematic review provided preclinical evidence of adverse effect of high iron intake in neonates on brain-health-related outcomes in adults [12]. …”
Section: To the Editormentioning
confidence: 99%
“…Particularly in populations living at HA this may expose to iron overload. Recently, a systematic review provided preclinical evidence of adverse effect of high iron intake in neonates on brain-health-related outcomes in adults [12]. …”
Section: To the Editormentioning
confidence: 99%
“…To determine a possible role for iron in microglial activation, we used the NIS model. This is relevant to understanding the mechanisms through which iron promotes HD and other disorders because the doses approximate what a human infant may receive and there is no detectable short--term toxicity (Agrawal et al, 2017). We have previously reported that NIS potentiates HD in the R6/2 and YAC128 mouse models (Berggren et al, 2015, Berggren et al, 2016.…”
Section: Neonatal Iron Supplementation Activates Microglial Cellsmentioning
confidence: 99%
“…This model is relevant, as in most populations human infants are supplemented with iron to prevent deficiency. Recommended daily allowances for iron have been developed to prevent iron deficiency, and upper limits were established to avoid short--term adverse effects (Micronutrients, 2001); however, long--term consequences of iron supplementation are not understood (Agrawal et al, 2017). We have previously shown that NIS in R6/2 and YAC128 mouse models of HD exacerbates disease progression (Berggren et al, 2015, Berggren et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Particularmente, en poblaciones que viven en la altura estas medidas bien intencionadas pueden exponer a una sobrecarga de hierro, que podría ser más bien perjudicial para la salud. Recientemente, una revisión sistemática da evidencia preclínica de efectos adversos que tiene en la salud cerebral en adultos la ingesta elevada de hierro en neonatos (51) .…”
Section: Reflexiones Finalesunclassified